Revolutionizing bone regeneration: advanced biomaterials for healing compromised bone defects - Awad, Kamal; Ahuja, Neelam; Yacoub, Ahmed S.; Brotto, Leticia; Young, Simon; Mikos, Antonios; Aswath, Pranesh; Varanasi, Venu (Frontiers in Aging, 2023)
In this review, we explore the application of novel biomaterial-based therapies specifically targeted towards craniofacial bone defects. The repair and regeneration of critical sized bone defects in the craniofacial region requires the use of bioactive materials to stabilize and expedite the healing process. However, the existing clinical approaches face challenges in effectively treating complex craniofacial bone defects, including issues such as oxidative stress, inflammation, and soft tissue loss. Given that a significant portion of individuals affected by traumatic bone defects in the craniofacial area belong to the aging population, there is an urgent need for innovative biomaterials to address the declining rate of new bone formation associated with age-related changes in the skeletal system. This article emphasizes the importance of semiconductor industry-derived materials as a potential solution to combat oxidative stress and address the challenges associated with aging bone. Furthermore, we discuss various material and autologous treatment approaches, as well as in vitro and in vivo models used to investigate new therapeutic strategies in the context of craniofacial bone repair. By focusing on these aspects, we aim to shed light on the potential of advanced biomaterials to overcome the limitations of current treatments and pave the way for more effective and efficient therapeutic interventions for craniofacial bone defects.